A efetividade da terapia fonoaudiológica de grupo para a redução da ansiedade de pacientes com disfonia - Trajano, Flávia Maiele Pedrosa (2015)
This dissertation is subdivided into three articles: the first one is a systematic review titled "Speech therapy group and its effectiveness for treatment of dysphonia: a systematic review", accepted for publication in CEFAC journal and had intended to conduct a review on systematic group of vocal therapy and its effects in patients with dysphonia. Through the study it was revealed that the group therapy method is effective for rehabilitation of dysphonia. The second article is also a systematic review entitled "Anxiety levels and impacts on voice: a systematic review", submitted to the journal Communication Disorders and features in order to perform a systematic review about anxiety and its impact on voice. The main finding of the study was the existence of a relationship between anxiety and presence of vocal changes. Finally, the third article built with empirical data from field research, has the title "The group speech therapy reduces anxiety of patients with dysphonia", will be submitted to the journal Folia Phoniatrica et Logopaedica and has the objective to analyzing the levels of anxiety pre and post-group therapy vocal symptoms in patients with dysphonia and verifying the correlation between vocal symptoms and anxiety levels. The study bought the existence of the correlation between anxiety levels and the voice, but also the effectiveness of group therapy for rehabilitation of these disorders.